Reconsidering Stress Patterns in English Blends - Eungyeong Kang; Jin-hyung Kim (Korean Journal of English Language and Linguistics, 2014)
Blends are words derived from two source words by snipping the middle part out, such as fantabulous (< fantastic + fabulous) and vodkatini (<vodka + martini). This paper examines the stress pattern of English blends and proposes that the stress pattern of the blend varies on the length of the right-hand source word (=W2) and its wordhood. Based on the data set of blends, we show that the stress pattern of the blend is determined by that of W2 when it is three syllables long or longer than that. However, W2 prominence in blend stress varies when W2 is disyllabic. When a splinter of W2 is in the blend, the stress pattern of the blend is determined by that of W2. When W2 is preserved in the blend as a complete word, blend stress is either on the initial syllable or follows W1 stress. When W2 is a complete monosyllabic word in the blend, stress falls on the initial syllable across the board. We propose that this is a case of a clipped compound. The variation in the stress patterns of the blends from a disyllabic W2 suggests that we are dealing with a continuum from blends to clipped compounds. We contend that W1 or W2 prominence with regard to blend stress is related to the recoverability of the source words from the splinters in the blend. KCI Citation Count: 3